RANCANGAN DAN ANALISIS STRUKTUR SUDU TURBIN ANGIN LPN 10000 E - Sulistyo Atmadi; Firman Hartono (Jurnal Teknologi Dirgantara, 2005)
Structure of the LPN 10000 E wind turbine blade has been manufactured and its structural analysis to find out the strenght of this structure during its operation has also been conducted. The method of aero bending moment and centrifugal bending moment and load has been used while neglegting frcitional and torsional load. The analysis is obtained for composite blade strengthened by high strength carbon unidirectional reinforcement composite. With safety factor of 1.3 minimum, it was concluded that the blade is strong enough to use at its designed operational load.